Animal Nutrition and Welfare in Sustainable Production Systems - Puvača, Nikola; Tufarelli, Vincenzo; Voslarova, Eva (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Today, food animal production systems demand high energy, land, chemicals, and water-all of which are increasingly becoming scarce. Thus, change and innovation are required in many animal production systems to meet the present and future demands for animal products sustainably. Over the last four decades, inexpensive grain, energy, and protein have enabled the economic development of intensive meat, eggs, and milk production systems based on feeding grains and other ingredients sourced from far-off places. The poultry and pig intensive production systems have become highly capital intensive, and they have resulted in many environmental challenges.Food animal feed, nutrition, and welfare are the foundation of successful animal systems. They directly or indirectly affect the entire animal production sector, associated services, public goods, and services, including animal productivity, health and welfare, product quality and safety, land use and land-use change, and greenhouse gas emissions. The sustainability of food animal nutrition and welfare is crucial in developing animal production across production systems. The sustainable increase in animal productivity, which is key to meeting the large current and future demands for animal origin products, cannot be achieved without sustainable animal nutrition and welfare.